Answer:
2x + 3y = 12 …equation 1
x– y = 1 … equation 2
To solve it by elimination method, let us multiply the second equation by 3
3x — 3y = 3 …equation 3
Now add the first and third equation
5x = 15
x = 3
From equation 2, y = x-1
y = 2
Hence x = 3, y = 2.
(b) 3x + y = 10
Since we have one equation and 2 variables, it cannot be solved by the elimination method.
To solve this, we can go for trial and error
Say y = 1, x = 3 or x = 5, y = —5
(c) x – 3y=1 …eq 1
3x – 2y + 4 = 0 …eq 2
Multiply eq 1 by 3, 3x — 9y = 3 …eq 3
Eq 2 — eq 3,
7y = —7
y = —1, x = —2 Ans